A Note on Lawley's Formulas for Standard Errors in Maximum Likelihood Factor Analysis - Jennrich, Robert I.; Thayer, Dorothy T.; Educational Testing Service, Princeton, NJ. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
Evidence is given to indicate that Lawley's formulas for the standard errors of maximum likelihood loading estimates do not produce exact asymptotic results. A small modification is derived which appears to eliminate this difficulty. (Author)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Error Patterns; Factor Analysis; Research Reports; Statistical Analysis; Tables (Data); Lawleys Formulas